The Impact of Assets on Firm Performance (Case Study on Football Club in Europe) - Kudratov Azizbek; Ida Farida Adi Prawira; Irsyad Fauzan Prasetia; Umarova Zulayho (Journal of Social Science and Humanities, 2026)
This study examines the effect of total assets on the firm value of football clubs. The commercialization of the football industry has transformed clubs into business entities, making firm value an important indicator for investors. Using a quantitative approach, this study analyzes secondary data from 10 football clubs over the period 2022–2025. Firm value is proxied by share price, while total assets are measured as the natural logarithm of total assets, and analyzed using simple linear regression. The results show that total assets do not have a significant effect on firm value, suggesting that asset size alone is not a key determinant. This study is limited by its small sample size; therefore, future research should include more samples and additional variables to provide a more comprehensive analysis.